TRADISI BIRAU SEBAGAI WADAH MEMBANGUN TOLERANSI MASYARAKAT BULUNGAN YANG MULTIKULTURAL. - Necklisya Roulice; Wahyu Djoko Sulistyo (UNZAH Genggong, 2021)
Abstract Multiculturalism or cultural diversity is something that we often see in Indonesia, one of which is in Bulungan district. Bulungan is a district that consists of several different cultures, one of the traditions that is very well known by the people in this district is the birau tradition. The Birau tradition is an annual agenda that is carried out as well as the anniversary of his birth in Bulungan Regency, this tradition displays various kinds of culture and competitions. The birau tradition can be said as a forum for creating tolerance among the multicultural Bulungan community because in this tradition there are no limits for anyone who wants to participate, even this tradition wants to show that diversity is a strong unity for the Bulungan community. Keywords: Multicultural, Tolerance, Bulungan, Birau Tradition